An approach into the detection of authenticity of black pepper (Piper nigrum L.) oleoresin - PUSHPA R KULKARNI, MILIND M MADAN, REKHA S SINGHAL, (Journal of Spices and Aromatic Crops, 1996)
Investigations on authenticity of black pepper (Piper nigrum) oleoresin indicated that saponification value, iodine value and ratio of saponification value to iodine value are useful indicators. The presence of papaya seeds in black pepper used to prepare the oleoresin could be detected at 15 per cent levels using these indices. The advantages of these indices over piperine as an indicator are discussed.